Characterization of Co0.5(Ti1−xZrx)0.5NbO4 microwave dielectric ceramics based on structural refinement. Issue 14 (1st October 2017) - Li, Yaoyao; Lu, Xiaochi; Zhang, Yan; Zou, Yanyan; Wang, Lixi; Zhu, Haikui; Fu, Zhenxiao; Zhang, Qitu
Abstract: Zr-substituted Co0.5 Ti0.5 NbO4 microwave dielectric ceramics with low losses were prepared by the conventional solid-state method. To obtain dense ceramics, sintering temperatures from 1000 °C to 1280 °C were systematically investigated. The microstructure and the microwave dielectric properties of the Zr-substituted Co0.5 Ti0.5 NbO4 ceramics were analyzed using different characterization techniques, including field-emission scanning electron microscopy (FESEM), X-ray diffraction (XRD), energy dispersive X-ray spectroscopy, Rietveld refinement and microwave dielectric measurements. Analyses showed that the dielectric properties are strongly dependent on the crystal structure, which causes densification of the microstructure of the ceramics. The structure of Zr-substituted Co0.5 Ti0.5 NbO4 ceramics transformed from tetragonal to monoclinic as substitution increased. Additionally, the permittivity( ɛ r ) declined from 64.3 to 24.4 due to a change in the polarizability. However, the quality factor( Q × f ) increased considerably. The temperature coefficient of the resonant frequency( τ f ) was near zero due tothe compounding of tetragonal structure with a positive τ f and monoclinic structure with a negative τ f . Optimal microwave dielectric properties in Zr-substituted Co0.5 Ti0.5 NbO4 included a ɛ r of 27.6, a Q × f of 40, 132.8 GHz and a τ f of 5.8 ppm/℃.